THE STUDY ON THE INCOME AND PURCHASING POWER OF NORTH SUMATERA PROVINCE - Lubis, Delima - (Advances in Social Sciences Research Journal, 2018)
Abstract:North Sumatra Province has been the central node of Indonesian economy growth in Sumatra of Indonesia. The development of this province affects the regional economy. This study aimed at finding the effect of income levels on the purchasing power of the people of North Sumatra. To find the economic and welfare of population in this province, an associative research approach was conducted. It sought the level of income per capita correlation to the purchasing power of North Sumatra Province. The data from Central Bureau of Statistic (BPS, 2016) in which economic transactions of 2007 – 2015 was realised. The data analyze technique was a simple linear regression equation. After the calculation and analysis , the results showed that the level of income has a positive and significant impact on people’s purchasing power in North Sumatra. It concluded the higher the income level of the North Sumatra population made the purchasing power increasing. So purchasing power was better if the income had beeen sufficient to meet the daily needs.